Spritualitas Kepemimpinan Kristen Dalam Pelayanan Naposo Gereja Kristen Indonesia Klasis Parlilitan - Tulus Tumanggor; Bernhardt Siburian; Nurelni Limbong; Erman Saragih; Ibelala Gea (STP Dian Mandala Gunungsitoli Nias Keuskupan Sibolga, 2024)
The purpose of this study is to determine the Importance of Naposo Leadership Spirituality in Service at GKI Sumut Parlilitan Classis. The research method in this researcher uses a qualitative research method by conducting interviews with Pastors, elders, paniroi, fathers, mothers, Naposo leaders, male youth, female youth. The data studied to examine the spiritual value of Christian leadership in the Naposo service of the Indonesian Christian Church Parlilitan Classis